1991
DOI: 10.1080/02724936.1991.11747530
|View full text |Cite
|
Sign up to set email alerts
|

Cutis laxa, growth retardation and hip dislocation in a Sudanese child

Abstract: This case report describes the rare variant of autosomal recessive cutis laxa with bone dystrophy in a Sudanese child. The clinical features include cutis laxa, growth and development retardation, facial dysmorphism, hyperextensible joints, dislocation of the hips and a large umbilical hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
1
Order By: Relevance
“…In literature, it's reported that three intermarriage family with CLS had 5 hip dislocations . [23] In the contrast of previously mentioned findings of the etiopathogenesis, we believe hip dysplasia of our patient may be incidental.…”
contrasting
confidence: 97%
“…In literature, it's reported that three intermarriage family with CLS had 5 hip dislocations . [23] In the contrast of previously mentioned findings of the etiopathogenesis, we believe hip dysplasia of our patient may be incidental.…”
contrasting
confidence: 97%